1992
DOI: 10.1091/mbc.3.8.875
|View full text |Cite
|
Sign up to set email alerts
|

A mutant nuclear protein with similarity to RNA binding proteins interferes with nuclear import in yeast.

Abstract: We have isolated mutants of the yeast Saccharomyces cerevisiae that are defective in localization of nuclear proteins. Chimeric proteins containing the nuclear localization sequence from SV40 large T-antigen fused to the N-terminus of the mitochondrial Fl3-ATPase are localized to the nucleus. Npl (nuclear protein localization) mutants were isolated by their ability to grow on glycerol as a consequence of no longer exclusively targeting SV40-F1f-ATPase to the nucleus. All mutants with defects in localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
153
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 68 publications
5
153
0
Order By: Relevance
“…HSS1 does not suppress the temperature-sensitivity of all sec63 mutations but is specific for the sec63-101 allele ( Figure 1B). HSS1 also does not suppress the temperature-sensitive phenotype of other ER translocation mutants ( Figure 1B), such as sec61-2, sec62-1, and kar2-159, or of npl4-1 (Bossie et al, 1992), another nuclear localization mutant.…”
Section: Specific Suppression Of Sec63-101 By Hss1mentioning
confidence: 90%
See 1 more Smart Citation
“…HSS1 does not suppress the temperature-sensitivity of all sec63 mutations but is specific for the sec63-101 allele ( Figure 1B). HSS1 also does not suppress the temperature-sensitive phenotype of other ER translocation mutants ( Figure 1B), such as sec61-2, sec62-1, and kar2-159, or of npl4-1 (Bossie et al, 1992), another nuclear localization mutant.…”
Section: Specific Suppression Of Sec63-101 By Hss1mentioning
confidence: 90%
“…Judging by indirect immunofluorescence using antibodies directed against Npl3p, a normally nuclear protein (Bossie et al, 1992) Figure 5. A myc-tag was introduced at the C-terminus of Hsslp as described in MATERIALS AND METHODS.…”
Section: Specific Suppression Of Sec63-101 By Hss1mentioning
confidence: 99%
“…We further analyzed the distribution of endogenous Nop1p (38) by indirect immunofluorescence microscopy. As representatives of a second class of nuclear proteins with noncanonical NLSs, we analyzed the distribution of endogenous Nab2p (39), Nab3p (40), Npl3p (33), and a normally nuclear fusion of Hrp1p (41) to GFP. Cells deleted for KAP123 also showed normal distribution of all nuclear proteins tested.…”
Section: Pse1 Is Essential For Growth and Has A Redundantmentioning
confidence: 99%
“…npll is allelic to sec63 [78], a known gene required for translocation across the ER membrane; npll mutants are defective in nuclear retention rather than nuclear transport. Mutants of np13 [79] and np16 [lo] alter the uptake of proteins into the nucleus with no apparent defect in nuclear retention. NPL3 encodes a nuclear protein with a glycine/arginine rich sequence typically found in several nucleolar proteins, and an RNA binding sequence [79].…”
Section: Genetic Screens For Nuclear Transport Mutantsmentioning
confidence: 99%
“…Mutants of np13 [79] and np16 [lo] alter the uptake of proteins into the nucleus with no apparent defect in nuclear retention. NPL3 encodes a nuclear protein with a glycine/arginine rich sequence typically found in several nucleolar proteins, and an RNA binding sequence [79]. It was suggested that the mutant NPL3 protein could bind to components of the nuclear transport machinery thereby interfering with the import of other karyophiles.…”
Section: Genetic Screens For Nuclear Transport Mutantsmentioning
confidence: 99%